Pelatihan Pengoperasian Drone sebagai Peningkatan Kompetensi Siswa SMK Kehutanan Negeri Pekanbaru - Ikhsani, Hanifah; Ikhwan, Muhammad; Sadjati, Emy (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
The utilization of drones for mapping is an easy, cheap and fast way with better spatial resolution when compared to conventional mapping or satellite rides. For students of SMK Kehutanan Negeri Pekanbaru, this ability is expected to improve their skills after graduating from forestry school. This service provides solutions including: 1) increase students' understanding of Drone Mapping, 2) increase the competence of SMK Kehutanan Negeri Pekanbaru students in the field of forest and land cover mapping. The service was carried out at SMK Kehutanan Negeri Pekanbaru. The service was conducted from December 2024 to May 2025. The activities carried out include socialization or delivery of material on various forms of drone utilization in the forestry sector, training in spatial data collection using drones, trials in processing spatial data from drone photos and map layout. After the service was carried out, there was an increase in the knowledge of partners who were students of SMK Kehutanan Negeri Pekanbaru on drone operation training activities as an increase in competence, an increase of 66.48%. Partners already have skills in utilizing drones for mapping. Partners are able to create flight paths, fly drones, process and layout maps.